Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2010)
This report by the external panel of experts ('the panel') examines the effectiveness and appropriateness of the safeguards policy over the ten years since the inception of the policy, and most particularly in the five years since its last review. Furthermore, the panel, drawing on its research and experience, aims to establish a course for the Executive Board to consider that would help the safeguards policy continually improve, adapt to changing world conditions, and remain viable and relevant for the next decade. In gathering data to form its opinion, the panel (i) consulted with stakeholders in the policy (including central bank authorities, IMF Executive Directors' offices, Fund and World Bank staff, and international audit firms), (ii) examined safeguards and other Fund-specific documents, and (iii) researched international reference materials.